The impact of reduced worktime on sleep and perceived stress – a group randomized intervention study using diary data - Schiller, Helena; Lekander, Mats; Rajaleid, Kristiina; Hellgren, Carina; Åkerstedt, Torbjörn; Barck-Holst, Peter; Kecklund, Göran (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVE ': 'Insufficient time for recovery between workdays may cause fatigue and disturbed sleep. This study evaluated the impact of an intervention that reduced weekly working hours by 25% on sleep, sleepiness and perceived stress for employees within the public sector. ' ' METHOD ': 'Participating workplaces (N=33) were randomized into intervention and control groups. Participants (N=580, 76% women) worked full-time at baseline. The intervention group (N=354) reduced worktime to 75% with preserved salary during 18 months. Data were collected at baseline and after 9 and 18 months follow-up. Sleep quality, sleep duration, sleepiness, perceived stress,and worries and stress at bedtime were measured with diary during one week per data collection. ' ' RESULT ': 'A multilevel mixed model showed that compared with the control group, at the 18-month follow-up, the intervention group had improved sleep quality and sleep duration (+23 minutes) and displayed reduced levels of sleepiness, perceived stress, and worries and stress at bedtime on workdays (P<0.002). The same effects were shown for days off (P<0.006), except for sleep length. Effect sizes were small (Cohen’s f2<0.08). Adding gender, age, having children living at home, and baseline values of sleep quality and worries and stress at bedtime as additional between-group factors did not influence the results. ' ' CONCLUSION ': 'A 25% reduction of weekly work hours with retained salary resulted in beneficial effects on sleep, sleepiness and perceived stress both on workdays and days off. These effects were maintained over an 18-month period. This randomized intervention thus indicates that reduced worktime may improve recovery and perceived stress.
Keywords: diary data; gender; perceived stress; public sector; randomized intervention; reduced worktime; sleep; sleep duration; sleep quality; sleepiness; stress; worktime